Reforming the Fiscal Framework. The Case of Sweden 1973-2013 - Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2014)
This paper explores the evolution of Swedish fiscal policy from one extreme approach to another one in less than four decades. After the demise of the Bretton Woods-system in the early 1970s, Swedish fiscal policy was based on a Keynesian approach with the goal to stabilize the business cycle and maintain full employment using a large set of instruments in a discretionary manner. In the wake of the deep financial crisis in the early 1990s, this policy paradigm was eventually replaced by a rule-bound scheme. A fiscal framework was set-up as an instrument to rein in public finances. The present goal of fiscal policy is to maintain sustainable public finances while avoiding discretionary measures.
Keywords: E52; E62; E63; E65; F44; H62; O52; 330; Fiscal rules; fiscal policy council; fiscal policy; policy learning; Sweden